The impact of macroeconomic determinants and tax form on inflation in selected Balkan countries - Milenković, Nada; Kalaš, Branimir; Mirović, Vera; Andrašić, Jelena (Serbian Journal of Management, 2019)
Our goal is to reflect how the gross domestic product, unemployment, real interest rate, savings, government expenditures and value-added tax effect on inflation in selected Balkan countries for period 2008-2016. Research examines the impact of macroeconomic determinants on price movements in the general level, measured by the annual rate of inflation. Selected countries are Albania, Bosnia and Herzegovina, Croatia, Montenegro, North Macedonia, Serbia and Slovenia. This paper includes model where inflation is the dependent variable, while gross domestic product, unemployment, real interest rate, saving, government expenditures and value-added tax represent independent variables. Authors used LLC test and VIF test for stationary and multicollinearity, where confirmed that model is adequately designed. Using Hausman test, fixed effect model is chosen, where results have shown that gross domestic product, unemployment and value-added tax have a statistically significant impact on inflation compared to other explanatory variables in the model.
Keywords: inflation; macroeconomic determinants; panel model; Balkan countries